Timing is Everything The Politics and Processes of New Zealand Defence Acquisition Decision Making - Greener, Peter (Canberra Papers on Strategy and Defence, 2009)
This book identifies the critical factors that shaped and influenced New Zealand's defence acquisition decision-making processes from the election of the Fourth Labour Government in 1984 and the subsequent ANZUS crisis, through to the 11 September 2001 terrorist attacks on the United States and the following 'war on terror'. It explores and analyses decision-making processes in relation to the ANZAC frigates, the military sealift ship HMNZS Charles Upham, the F-16 strike aircraft, the P-3C Orion maritime patrol aircraft upgrade, and the LAV IIIs.